Unraveling the physics of connectivity and dispersal in Mediterranean coastal marine populations: the case of the Alboran and Adriatic seas - Nadal Arizo, Irene (UMA Editorial, 2025)
Hydrodynamic features play a crucial role in shaping the dispersal and connectivity of fish populations, especially in highly dynamic regions influenced by currents, river outflows, and meteorological fluctuations. Understanding how species interact with these physical processes is essential for managing vulnerable populations and identifying areas that require targeted conservation. This study focuses on the hydrodynamics that drive connectivity in the Alboran and Adriatic Seas, two key areas for protection within the Mediterranean Sea. Using a high-resolution hydrodynamic model coupled with a Lagrangian tracking module, three case studies are examined: (1) eggs and larvae of blackspot seabream, (2) generic marine organisms inhabiting the region, and (3) the invasive algae Rugulopteryx okamurae. Lagrangian particles representing these organisms are released across the basin under varying conditions to map their likely dispersal pathways. Different methodologies are applied over varying pelagic durations to capture the temporal dimension of connectivity. The study discusses the implications of these findings for improving species management and assessment in the Mediterranean.
Keywords: Circulación oceánica - Tesis doctorales; Connectivity; Dispersal; Physical oceanography; Alboran Sea; Adriatic Sea